Correlation of hemoglobin level and platelets count in anemic and non-anemic patients attending Madhesh Institute of Health Sciences (MIHS), Nepal (Rajarshi Janak University Research Journal, 2025)
Introduction: Anemia is a condition characterized by a reduced number of red blood cells or lower levels of hemoglobin.  The World Health Organization estimates that 1.62 billion individuals globally are affected by anemia, which represents 24.8 percent of the population, highlighting its significant public health concern in both developing and developed nations. Platelets play a vital role in maintaining homeostasis and are often affected by underlying hematological conditions including anemia. The relationship between anemia and platelet count is complicated and is poorly understood. The study aimed to assess the hemoglobin level and platelets count among patients visiting tertiary level care center of Madhesh Province, Nepal and evaluate their association in anemic and non-anemic patients.Methodology: The hospital based cross-sectional comparative study was conducted among 350 patients visiting tertiary care center to analyze blood samples for hemoglobin level and platelet counts and their correlation was assessed.Result: The mean hemoglobin level was 9.97 ± 1.54 g/dL in anemic individuals and 13.46 ± 1.95 g/dl in non-anemic individuals. Platelet counts were 1.81 ± 0.96 lakhs/µl in anemic and 2.03 ± 0.73 lakhs/µl in non-anemic individuals. Anemia found more prevalence in females (36.85%), underweight (15.14%), and vegetarians (34.28%). In overall patients, a weak  positive correlation was observed between hemoglobin and platelet count (r = 0.10, p = 0.047) while a very strong positive correlation was observed among anemic patients(r=0.975, p=0.002).Conclusion: Anemia was found more prevalent in females, underweight and vegetarians as well as a very strong positive correlation between hemoglobin levels and platelets counts were observed among anemic patients.